Challenges for Study Centers in an Electronic Age: A case study of the Center for Distance Education at Carl von Ossietzky University of Oldenburg in Germany - Bernath, Ulrich J.; Kleinschmidt, Axel C.; Walti, Christine J.; Zawacki, Olaf (International Review of Research in Open and Distributed Learning, 2003)
This paper reports on developments in study centers in Germany and in particular the experience of the Center for Distance Education at Carl von Ossietzky University of Oldenburg. Emphasis in this paper has been placed on the challenges faced by German universities in the electronic age, which in its early stages began in 1995. The purpose of this paper is to ground the establishment of open and distance study centres vis-à-vis the unique cultural and institutional circumstances characteristic of Germany and its institutions of higher education.